Розвиток державної системи професійно-ремісничої освіти УСРР у період НЕПу (1921-1928 рр. ) - Малишев, О.В. (Історичний архів. Наукові студії, 2014)
Показано причини та умови розвитку державної системи професійно-ремісничої освіти.
Охарактеризовано етап її планування, перераховано та всебічно охарактеризовано
основні типи проектованих навчальних закладів. Виявлено типи навчальних закладів, які
були реально засновані. Названо їх кількість, визначено рівень фінансування, досліджено
питання набору абітурієнтів, пріоритетні напрями підготовки учнів, їх соціальний склад,
роль кооперативних організацій у розвитку державної системи професійно-ремісничої
освіти. Показаны причины и условия развития государственной системы профессионально-
ремесленного образования. Охарактеризован этап ее планирования, перечислены и
всесторонне охарактеризованы основные типы проектировавшихся учебных заведений.
Выявлены типы учебных заведений, которые были реально учреждены. Названо их коли-
чество, определен уровень финансирования, рассмотрены вопросы набора абитуриентов,
приоритетных направлений подготовки учащихся, их социального состава, роли коопера-
тивных организаций в развитии государственной системы профессионально-ремеслен-
ного образования. Small business is a part of economic of modern Ukraine. It originated in the handicraft
industry of the late 19th – early 20th centuries. The state professional and craft educational
establishments prepared personnel for it. It had been functioning in a period of NEP in 1921-
1928. The main reasons of it’s appear and develop were beginning of the NEP and lack of
qualified personnel in handicraft. The development of state system of professional and craft
education was due to the large number of pre-revolutionary schools of this profile and progress
of petty commodity production in 1921-1929. It was planned to create such types of state
professional and craft educational establishments as like instructor item artisanal training
courses, educational and handicraft workshops artisanal vocational school, artisanal courses
instructors. Besides the training they provide indoctrination of students. Handicraft shops,
handicraft and industrial schools and artisanal courses of instructors had been functioning and
founded in USSR in 1921-1929. There were 116 establishments by 1928. The allocation for its
needs was about 3,5 billiards rubles. The contest in government handicraft workshops and
schools was up to 2 people in a one place. The main streams of study of students were forging,
plumbing and carpentry mastery. The social composition of students consisted of peasant
children (50,4 %), workers children (17,6 %) and children of artisanal (14 %). The role of cooperative
organizations in the development of the USSR State system of professional handicraft
education was insignificant. The main problems of state handicraft workshops, schools and
courses were the lack of funding, poor coordination of state and cooperative organizations, lack
of employment of graduates, the low activity of the Party and Komsomol organizations of
students.